Controlling dielectric loss of biodegradable black phosphorus nanosheets by iron-ion-modification for imaging-guided microwave thermoacoustic therapy. (August 2022) - Chen, Xiaoyu; Zhang, Shanxiang; Liu, Jiaqian; Ren, Mingyang; Xing, Da; Qin, Huan
Abstract: Microwave-induced thermoacoustic (TA) technology transforms microwave into acoustic waves useable for imaging or therapy, based on the power density of the pulsed microwaves. Exploiting nanoparticles with high biocompatibility, safe metabolism, and high microwave-acoustic conversion is the key to the clinical translational application of TA therapy. In this paper, we proposed a biodegradable and high microwave absorption nanoparticle for TA therapy. The proposed nanoparticle uses iron ions to regulate the atomic defects of biodegradable black phosphorus (BP) nanosheets to augment the dielectric loss. The iron ions adsorb with the lone pair electrons indicated of BP through the conjugated π bond to increase the permanent electric dipoles. With pulsed microwave irradiation, a large number of electric dipoles are repeatedly polarized, causing instantaneous temperature rise and then generating significant TA shockwave via TA cavitation effect. TA shockwave can disrupt cell membranes in situ to trigger programmed apoptosis and produce precise anti-tumor effects. Additionally, the nanoparticle-mediated TA process generates images that deliver valuable data, such as the size, shape, and location of the tumor for treatment planning and monitoring. This hypothesis has been tested in vitro and in vivo with animal models of glioblastoma tumors. The experimental results demonstrate the high theragnostic efficiency for tumor inhibition and TA imaging, exhibiting low systemic cytotoxicity and good biocompatibility after systemic administration. The established BP-based nanoparticle with both safe metabolism and high microwave-acoustic conversion is a promising candidate for precision theranostics without obvious side effects.